Numerical Study on Shock/Droplet Interaction Before a Standing Wall (Communications in Computational Physics, 2020)
In this work, numerical simulations have been performed to study the shock/droplet interaction before a standing wall. The research efforts are directed to revealthe influence of the reshock on the flow features and interfacial dynamics. A five-equationmodel is applied to model the compressible multi-fluid flow with movinginterface. The governing equations are solved under an axisymmetric assumption usinga finite volume method. By varying the incident shock Mach number ($M_S$) andthe distance (L) between the droplet and the wall, the wave motion and the dropletdeformation are closely examined for four typical simulations. Also, the underlyingphysics of some salient flow features and interfacial behavior is discussed. Moreover,the maximum wall pressure is monitored in term that structural damage is possiblyinduced to the wall as a result of the shock/droplet interaction. The droplet kinematicsis examined via the center-of-mass displacement and velocity, to clarify the integraleffects of changing $M_S$ and L.